Analysis Of Optimal Portfolio Formation Using A Model Markowitz On LQ-45 Stocks - Fitriani Rahim; Naura Wafiyah; Muhammad Akram Zaki Irfan; A. Nur Habibie Jannah; Reshki (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study aims to analyze the construction of an optimal investment portfolio using the Markowitz Model for stocks listed in the LQ-45 index. The LQ-45 stocks were chosen because they represent leading and highly liquid companies on the Indonesia Stock Exchange, consisting of diverse industrial sectors that provide broad opportunities for risk reduction through diversification. The research method includes the calculation of expected returns, standard deviations as a measure of risk, and covariance among selected stocks to examine the interrelationship of asset movements. These components are then used to determine the optimal portfolio composition that offers the maximum possible return for a given level of risk or, conversely, minimizes risk for a targeted expected return. The results of the analysis demonstrate that the Markowitz Model is effective in forming portfolios that align with different investor risk preferences. The diversification effect generated by combining stocks across various sectors significantly reduces unsystematic risk without diminishing return potential. The findings also indicate that an optimal portfolio constructed using this method can serve as a practical and strategic investment alternative for both individual and institutional investors, particularly in a volatile market environment. Furthermore, this study provides valuable insights into portfolio selection strategies that can support investment managers in developing evidence-based decision-making frameworks. By applying modern portfolio theory, investors can better understand risk–return trade-offs and improve the efficiency of their investment allocations in the Indonesian capital market.